Endophyte infection influences disappearance of perennial ryegrass seed - Popay, A.; Marshall, S.; Baltus, J. (New Zealand Plant Protection, 2000)
bare ground was compared with that of seed infected by the fungal endophyte Neotyphodium lolii in four field trials One trial included clover seed and two trials contained seed infected with two different endophytes Infection with either endophyte significantly reduced seed disappearance and increased survival of seed to germination Clover seed disappeared at a similar rate to endophytefree ryegrass seed Bird netting reduced seed disappearance of all treatments but in most cases not significantly so Feeding by black field cricket nymphs and adults small field cricket adults and black beetle adults on ungerminated and newly germinated endophyteinfected and endophytefree seed was tested in the laboratory It was concluded that none of these insects caused the differences in seed disappearance observed in the field